Concepções sobre os processos de ensino e de aprendizagem de Matemática: um estudo de caso com professores graduados em áreas afins - Zocolotti, Alexandre Krüger (2015)
The research presented here focused on investigating conceptions of the processes of teaching and learning mathematics teachers trained in areas related to this discipline and who have attended a course in Educational Complementation. An empirical study was conducted with four teachers of mathematics - two teachers who worked in the Secondary School and two teachers who worked in high school - who had training in those molds. The theoretical study involved conceptions, teaching knowledge and training of mathematics teachers, with special attention to the models of teacher education in force in Brazil. For data collection, two different elements were used: semistructured interviews and observations of the practice of each of the surveyed teachers. In the data analysis, it was perceived details that have identified how each participant understands the processes of teaching and learning of mathematics. These details, which combine aspects that reveal knowledge of each of the teachers showed differences in expressed or mathematical knowledge in everyday practice observed, each of the participants. The conclusion of the study highlights the need for a discussion on the restructuring of Pedagogical Supplementary courses, as well as the urgency of a survey that reveals, at national level, the number of mathematics teachers who have been trained through these courses